2019
DOI: 10.1128/aac.02388-18
|View full text |Cite
|
Sign up to set email alerts
|

False-Positive Carbapenem-Hydrolyzing Confirmatory Tests Due to ACT-28, a Chromosomally Encoded AmpC with Weak Carbapenemase Activity from Enterobacter kobei

Abstract: In Enterobacter cloacae complex (ECC), the overproduction of the chromosome-encoded cephalosporinase (cAmpC) associated with decreased outer membrane permeability may result in carbapenem resistance. In this study, we have characterized ACT-28, a cAmpC with weak carbapenemase activity, from a single Enterobacter kobei lineage. ECC clinical isolates were characterized by whole-genome sequencing (WGS), susceptibility testing, and MIC, and carbapenemase activity was monitored using diverse carbapenem hydrolysis m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 32 publications
0
22
0
1
Order By: Relevance
“…Very recently, Jousset et al showed that E. cloacae can chromosomally encode an AmpC enzyme of the type ACT-28. Kinetic parameters of purified ACT-28 revealed a slightly increased imipenem hydrolysis compared to that of ACT-1 [177]. CMY-10 was the first reported carbapenemase among plasmidic class C β-lactamases, and this enzyme was also a class C ESBL with extended substrate specificity for extended-spectrum cephalosporins [178].…”
Section: Emerging Ambler Class C Carbapenemasesmentioning
confidence: 96%
“…Very recently, Jousset et al showed that E. cloacae can chromosomally encode an AmpC enzyme of the type ACT-28. Kinetic parameters of purified ACT-28 revealed a slightly increased imipenem hydrolysis compared to that of ACT-1 [177]. CMY-10 was the first reported carbapenemase among plasmidic class C β-lactamases, and this enzyme was also a class C ESBL with extended substrate specificity for extended-spectrum cephalosporins [178].…”
Section: Emerging Ambler Class C Carbapenemasesmentioning
confidence: 96%
“…Class C β-lactamases, also known as cephalosporinases, have been rarely reported as carbapenemases. To date, only two β-lactamases were described possessing a carbapenemase activity being CMY-10 and more recently ACT-28 ( 109 , 110 ).…”
Section: Minor Class C Carbapenemasesmentioning
confidence: 99%
“…Notably, E. nimipressuralis CIP 104980 (clinical), E. hormaechei ATCC 49162 (sputum of a male patient), E. ludwigii EN-119 (clinical) and E. kobei JCM 8580 (clinical) sequenced in this study encode well-defined T6SSs containing vgrG and hcp proteins as orphan components. Several studies have reported the niche, antibiotic resistance and virulence of E. kobei and E. ludwigii, which are most commonly isolated from human clinical specimens [28][29][30] . Although these strains are most commonly associated with clinical specimens, variations in loci containing regulatory proteins such as prpC or prpK, hcp and vgrG have been observed, showing that these strains encode functional T6SSs.…”
Section: Genome Wide Gene Prediction and Analysis Of Virulent Genes mentioning
confidence: 99%
“…This notable expression was observed in all Ecc-type strains with little variation. The imp operon is a conserved part of almost all T6SSs and actively participates in mediating hcp secretion 9,30 . The high expression of the imp operon and prpC under in vivo mimicking conditions revealed that the imp operon seems to play a very active role in virulence and host-microbe interactions and is fully functional.…”
Section: Genome Wide Gene Prediction and Analysis Of Virulent Genes mentioning
confidence: 99%